Cyber Physical Systems Approach to Power Electronics Education - Marko Vekić; Zoran Ivanović; Vladimir Katić; Ivan Čelanović; Stevan Grabić; Nikola Čelanović (Electronics, 2012)
This paper proposes a Cyber Physical Approach (CPS) to power electronics (PE) education where all aspects of PE technology from circuit topology to the implementation of real time control code on a microprocessor are dealt with as an inseparable whole, and only the system complexity is increased during the course of instruction. This approach is now made practical thanks to the affordable and unrestricted access to high-power PE laboratory infrastructure (PE laboratory in a box) in the form of high-fidelity digital PE emulators with 1us calculation time step and latency.